Role of the Wnt Pathway in Thyroid Cancer - Sastre-Perona, Ana; Santisteban, Pilar (Frontiers in Endocrinology, 2012)
Aberrant activation of Wnt signaling is involved in the development of several epithelial tumors. Wnt signaling includes two major types of pathways: (i) the canonical or Wnt/β-catenin pathway; and (ii) the non-canonical pathways, which do not involve β-catenin stabilization. Among these pathways, the Wnt/β-catenin pathway has received most attention during the past years for its critical role in cancer. A number of publications emphasize the role of the Wnt/β-catenin pathway in thyroid cancer. This pathway plays a crucial role in development and epithelial renewal, and components such as β-catenin and Axin are often mutated in thyroid cancer. Although it is accepted that altered Wnt signaling is a late event in thyroid cell transformation that affects anaplastic thyroid tumors, recent data suggest that it is also altered in papillary thyroid carcinoma (PTC) with RET/PTC mutations. Therefore, the purpose of this review is to summarize the main relevant data of Wnt signaling in thyroid cancer, with special emphasis on the Wnt/β-catenin pathway.